2017
DOI: 10.1298/ptr.e9923
|View full text |Cite
|
Sign up to set email alerts
|

The coordination of joint movements during sit-to-stand motion in old adults: the uncontrolled manifold analysis

Abstract: ABSTRACT. Objective: Sit-to-stand motion (STS) is a dynamic motion utilized in fundamental activities of daily living and requires extensive joint movement in the lower extremities and the trunk and coordination of multiple body segments. The present study aimed to investigate whether aging affects the motor coordination of joint movements required to stabilize the horizontal and vertical movement of center of mass using the uncontrolled manifold (UCM) analysis. Method: We recruited 39 older adults with no mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…An index of synergy was used to reflect the amount of co-variation among elemental variables that reduced the variability of a task-specific salient performance variable. The UCM approach has been used to investigate the stability of vertical posture across various motor tasks performed by unimpaired and impaired populations [17, 18]. In this study, groups of coactive muscles with proportional scaling of activation levels were defined as muscle modes (M-modes).…”
Section: Introductionmentioning
confidence: 99%
“…An index of synergy was used to reflect the amount of co-variation among elemental variables that reduced the variability of a task-specific salient performance variable. The UCM approach has been used to investigate the stability of vertical posture across various motor tasks performed by unimpaired and impaired populations [17, 18]. In this study, groups of coactive muscles with proportional scaling of activation levels were defined as muscle modes (M-modes).…”
Section: Introductionmentioning
confidence: 99%
“…This might have been a consequence of their independent assessment. The coordination of each joint and various factors affected the standing motion [19,20]. Therefore, this relationship could not be extracted by comparing the various items.…”
Section: Discussionmentioning
confidence: 99%
“…In our UCM analysis, segment CoM does not contain orientation information, which may play a role in contribution to postural coordination especially during turning or twisting motions even though it may not be critical in the perturbation-induced stepping movement in the current study design. Even though previous studies using UCM analysis investigated joint angles in relation to whole-body CoM control 5,48 , the quantification of wholebody CoM using multi-segment CoMs proposed in the current study may provide a more accurate measurement than using joint angles: both approaches require estimations of inertia properties such as segment mass and moment of inertia which propagate errors throughout the calculations for whole-body CoM estimation. However, joint angle calculations require additional estimation of joint centers, which may result in inflated uncertainty in calculation of the whole-body CoM.…”
Section: Limitationsmentioning
confidence: 97%
“…The concept of motor synergies has been proposed as a control mechanism of the CNS 3 , which refers to task-specific patterns of the multi-degrees of freedoms (DoFs) that stabilize the performance of a particular motor task 4 . Cumulating evidence on postural control has suggested that the CNS is able to synergistically control multiple DoFs such as multiple segments, multiple muscles, and multiple fingers for the stabilization of their combined actions such as whole body center of mass 5,6 , overall muscle activations 7,8 , and multi-finger grasping 9,10 .…”
mentioning
confidence: 99%